The Consequences of School Environment and Locus of Control on Adulthood Deviant Behavior. Issue 9 (1st September 2016) - Pals, Heili; Love, Tony P.; Hannibal, Bryce; Waren, Warren
ABSTRACT: We examine the long-term effect of school environment on individual deviant behavior. Specifically, we contrast the effects of school deviance and students' perception of school deviance on personal deviance later in life. Using longitudinal data from four waves of more than 3, 100 participants in the Kaplan Longitudinal and Multigenerational Study, we are able to show that school deviance in 7th grade has only a short-term effect on individual deviance. However, when students perceive a lack of deviance in their school at 7th grade, it decreased their personal deviance in their mid-forties if they were both deviant in 7th grade and reported an external locus of control.